Integration of traditional Chinese music: an evaluation of the interactive influence between traditional music and aesthetic thought - Yi Zhou; Feng Yu (Trans/Form/Ação)
Traditional Chinese music had a long history, with rich and extensive aesthetic concepts. The integration of traditional music and aesthetic ideas has a significant impact on the formation of China’s traditional music system. This article explored the interactive influence of traditional music and aesthetic ideas, and elaborated on the musical ideas in traditional Chinese aesthetics. The content of musical aesthetic ideas of Confucianism, Taoism and Mohism was discussed, and the position of aesthetic ideas in traditional Chinese music was analyzed. By combing and analyzing the relevant literature, ancient books and historical materials, it is possible to understand the historical evolution and mutual influence of traditional music and aesthetic thought. Traditional aesthetic concepts not only played an important role in the development of Chinese music, but also played an undeniable role in promoting the development of Chinese music over thousands of years of history. This article aimed to explore the interaction between traditional music and aesthetic ideas, as well as the impact of traditional aesthetics on music, in order to promote the integration and development of traditional music and aesthetic ideas. In the evaluation of the interaction between traditional music and aesthetic thought, there may be a situation that the concept is too simplified. The relationship between traditional music and aesthetic thought is very complicated, involving many schools, historical periods and regions. It may not be able to fully cover all the influencing factors if it is only summarized by Confucianism, Taoism and Buddhism. It is suggested that the education and inheritance of traditional music and aesthetic ideas should be strengthened in music education. More traditional music artists and aesthetic theorists should be cultivated, so that they can pass on traditional music and aesthetic ideas to future generations and continue to develop and innovate in contemporary society.